Construction of fowlpox virus vectors with intergenic insertions: expression of the beta-galactosidase gene and the measles virus fusion gene. - Spehner, D (1990)
A DNA fragment from fowlpox virus cloned on a plasmid vector was modified to contain foreign DNA inserts within an intergenic region. In a first step, a 32-base-pair intergenic region from the fowlpox virus genome corresponding to the position of the thymidine kinase locus in the vaccinia virus genome was enlarged to 55 base pairs by site-directed mutagenesis. A unique restriction endonuclease site introduced upstream of the intergenic region was then used to insert various foreign DNA fragments. The lacZ gene encoding beta-galactosidase and the measles virus gene encoding the fusion protein were positioned downstream of two vaccinia virus p7.5 promoter elements in either a direct repeat or inverted repeat orientation. Foreign DNA inserts contained within the fowlpox virus sequence were transferred to the viral genome by homologous recombination occurring in cells infected with a fowlpox virus temperature-sensitive mutant and transfected with both wild-type viral DNA and plasmid DNA. Recombinant viruses were selected for the expression of beta-galactosidase activity by screening for blue plaques in the presence of a chromogenic substrate. Stable recombinants expressing both the lacZ gene and the unselected measles gene were obtained when the p7.5 promoter was present as an inverted repeat. However, when the p7.5 promoter was in the direct repeat orientation, viral recombinants which initially expressed both gene inserts readily deleted the lacZ gene flanked by the promoter repeat. The methods described enable precise insertion and deletion of foreign genes in the fowlpox virus genome and could be applied to other intergenic regions of the same virus as well as other poxviruses.